2010
DOI: 10.1093/jmicro/dfq032
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying transient states in materials with the dynamic transmission electron microscope

Abstract: (250 words)The Dynamic Transmission Electron Microscope (DTEM) offers a means of capturing rapid evolution in a specimen through in-situ microscopy experiments by allowing 15 ns electron micrograph exposure times. The rapid exposure time is enabled by creating a burst of electrons at the emitter by ultraviolet pulsed laser illumination. This burst arrives a specified time after a second laser initiates the specimen reaction. The timing of the two Q-switched lasers is controlled by highspeed pulse generators wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Under these circumstances, solid Al grows into a superheated liquid throughout the entire solidification process. 1 This result is in good agreement with conventional solidification theory [15,16] of solid growth into a superheated liquid, which predicts stable, texture-less growth by propagation of a planar liquid-solid interface and provides in situ experimental verification for the first time with nm spatial resolution that the morphology of the liquid solid interface during rapid solidification of the metal can be explained by conventional solidification theory [15,16].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Under these circumstances, solid Al grows into a superheated liquid throughout the entire solidification process. 1 This result is in good agreement with conventional solidification theory [15,16] of solid growth into a superheated liquid, which predicts stable, texture-less growth by propagation of a planar liquid-solid interface and provides in situ experimental verification for the first time with nm spatial resolution that the morphology of the liquid solid interface during rapid solidification of the metal can be explained by conventional solidification theory [15,16].…”
Section: Resultssupporting
confidence: 83%
“…A 50 nm thick SiO 2 layer was used as a laser transparent cap layer. In situ melting experiments were performed in the dynamic transmission electron microscope (DTEM) [1,13,14] at Lawrence Livermore National Laboratory. The DTEM uses a YAG laser with wavelength ¼ 1064 nm to provide a thermal stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exothermic intermixing of Ni and Al in the liquid layer appears as the main mechanism driving the self‐sustaining propagation in the reactive Ni/Al nanofoils. In situ studies, both XRD and DTEM, support this hypothesis . Moreover, by investigating the applicability of the model, Turlo et al demonstrated that the reactive dissolution of Ni into liquid Al may be the only driving mechanism for propagation in the case of equiatomic Ni/Al RMNFs with a bilayer thickness less than 54 nm.…”
Section: Modeling Approachmentioning
confidence: 94%
“…Diffraction techniques are used to determine the local composition along the front. On the other hand, in situ observations within the dynamic TEM have revealed microstructure changes and local melting events during reaction propagation …”
Section: Methodsmentioning
confidence: 99%